How do you solve \[{{x}^{2}}-7x-6=0\] using the quadratic formula?
Answer
Verified
438.6k+ views
Hint: Compare the given quadratic equation with the general form given as: - \[a{{x}^{2}}+bx+c=0\]. Find the respective values of a, b and c. Now, find the discriminant of the given quadratic equation by using the formula: - \[D={{b}^{2}}-4ac\], where ‘D’ is the notation for the discriminant. Now, apply the formula: - \[x=\dfrac{-b\pm \sqrt{D}}{2a}\] and substitute the required values to get the answer.
Complete step by step solution:
Here, we have been provided with a quadratic equation: - \[{{x}^{2}}-7x-6=0\] and we are asked to solve it. That means we have to find the values of x. So, let us apply the discriminant method to solve the given quadratic equation.
Now, comparing the general form of a quadratic equation: - \[a{{x}^{2}}+bx+c=0\] with the given equation: \[{{x}^{2}}-7x-6=0\], we can conclude that, we have,
\[\Rightarrow \] a = 1, b = -7 and c = -6.
Applying the formula for discriminant of a quadratic equation given as: - \[D={{b}^{2}}-4ac\], where ‘D’ is the discriminant, we get,
\[\begin{align}
& \Rightarrow D={{\left( -7 \right)}^{2}}-4\times 1\times \left( -6 \right) \\
& \Rightarrow D=49+24 \\
& \Rightarrow D=73 \\
\end{align}\]
Now, we know that the solution of a quadratic equation in terms of its discriminant value is given as: -
\[\Rightarrow x=\dfrac{-b\pm \sqrt{D}}{2a}\]
So, substituting the given values and obtained values of D, we get,
\[\begin{align}
& \Rightarrow x=\dfrac{-\left( -7 \right)\pm \sqrt{73}}{2\times 1} \\
& \Rightarrow x=\dfrac{7\pm \sqrt{73}}{2} \\
\end{align}\]
(i) Considering (+) sign we have,
\[\Rightarrow x=\dfrac{7+\sqrt{73}}{2}\]
(ii) Considering (-) sign we have,
\[\Rightarrow x=\dfrac{7-\sqrt{73}}{2}\]
Hence, the above two values of x are the roots or solution of the given quadratic equation.
Note:
One may note that we will not be able to use the middle term split method to solve the question. This is because it will be difficult for us to think of the factors like: \[\left( x-\dfrac{7-\sqrt{73}}{2} \right)\] and \[\left( x-\dfrac{7+\sqrt{73}}{2} \right)\]. You may apply the third method known as completing the square method to solve the question. In this method we have to convert the equation \[a{{x}^{2}}+bx+c=0\] into the form: - \[{{\left( x+\dfrac{b}{2a} \right)}^{2}}=\dfrac{D}{4{{a}^{2}}}\] and then by taking the square root we need to solve for the value of x. Remember that the discriminant formula is derived from completing the square method.
Complete step by step solution:
Here, we have been provided with a quadratic equation: - \[{{x}^{2}}-7x-6=0\] and we are asked to solve it. That means we have to find the values of x. So, let us apply the discriminant method to solve the given quadratic equation.
Now, comparing the general form of a quadratic equation: - \[a{{x}^{2}}+bx+c=0\] with the given equation: \[{{x}^{2}}-7x-6=0\], we can conclude that, we have,
\[\Rightarrow \] a = 1, b = -7 and c = -6.
Applying the formula for discriminant of a quadratic equation given as: - \[D={{b}^{2}}-4ac\], where ‘D’ is the discriminant, we get,
\[\begin{align}
& \Rightarrow D={{\left( -7 \right)}^{2}}-4\times 1\times \left( -6 \right) \\
& \Rightarrow D=49+24 \\
& \Rightarrow D=73 \\
\end{align}\]
Now, we know that the solution of a quadratic equation in terms of its discriminant value is given as: -
\[\Rightarrow x=\dfrac{-b\pm \sqrt{D}}{2a}\]
So, substituting the given values and obtained values of D, we get,
\[\begin{align}
& \Rightarrow x=\dfrac{-\left( -7 \right)\pm \sqrt{73}}{2\times 1} \\
& \Rightarrow x=\dfrac{7\pm \sqrt{73}}{2} \\
\end{align}\]
(i) Considering (+) sign we have,
\[\Rightarrow x=\dfrac{7+\sqrt{73}}{2}\]
(ii) Considering (-) sign we have,
\[\Rightarrow x=\dfrac{7-\sqrt{73}}{2}\]
Hence, the above two values of x are the roots or solution of the given quadratic equation.
Note:
One may note that we will not be able to use the middle term split method to solve the question. This is because it will be difficult for us to think of the factors like: \[\left( x-\dfrac{7-\sqrt{73}}{2} \right)\] and \[\left( x-\dfrac{7+\sqrt{73}}{2} \right)\]. You may apply the third method known as completing the square method to solve the question. In this method we have to convert the equation \[a{{x}^{2}}+bx+c=0\] into the form: - \[{{\left( x+\dfrac{b}{2a} \right)}^{2}}=\dfrac{D}{4{{a}^{2}}}\] and then by taking the square root we need to solve for the value of x. Remember that the discriminant formula is derived from completing the square method.
Recently Updated Pages
Master Class 10 General Knowledge: Engaging Questions & Answers for Success
Master Class 10 Computer Science: Engaging Questions & Answers for Success
Master Class 10 Science: Engaging Questions & Answers for Success
Master Class 10 Social Science: Engaging Questions & Answers for Success
Master Class 10 Maths: Engaging Questions & Answers for Success
Master Class 10 English: Engaging Questions & Answers for Success
Trending doubts
Assertion The planet Neptune appears blue in colour class 10 social science CBSE
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE